Infantile Abdominal and Pelvic Lipoblastomas: A Case Series - Riccardo Guanà; Salvatore Garofalo; Luisa Ferrero; Maria Grazia Cortese; Luca Lonati; Elisabetta Teruzzi; Eleonora Basso; Isabella Morra; Riccardo Lemini; Nicola Sardi; Fabrizio Gennari (Georg Thieme Verlag KG, 2019)
Abstract Lipoblastomas are rare benign mesenchymal tumors that arise from embryonal fat cells. They are usually discovered in infants and children under 3 years of age, and mostly occur in the trunk (from 10 to 60%, depending on the study) and extremities (from 40 to 45%), while head and neck localizations are rare, with only five cases described to date. We report on three cases of lipoblastomas in infants younger than 4 years, with unusual localizations: one intra-abdominal, discovered during a laparotomy for an intussusception; one pelvic, misdiagnosed as an ovarian mass; and one gluteal with a pelvic extension. All children underwent magnetic resonance imaging as preoperative workup. All tumors were completely resected with free surgical margins and ultrasonographic follow-up was uneventful for all patients.